2011
DOI: 10.1007/s00701-011-1239-3
|View full text |Cite
|
Sign up to set email alerts
|

Cement leakage as a possible complication of balloon kyphoplasty—is there a difference between osteoporotic compression fractures (AO type A1) and incomplete burst fractures (AO type A3.1)?

Abstract: Cement leakages remain a problem in BKP. Although there was no significant difference between AO type A3.1 and all A1 fractures, subgroup analysis revealed a statistically significant higher risk of cement extrusions in A3.1 compared to A1.1 fractures. None of the affected patients showed new neurological deficits due to cement extravasations. Still, balloon kyphoplasty can be considered a safe procedure, even in the treatment of painful osteoporotic vertebral fractures of AO type A3.1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 28 publications
0
31
0
Order By: Relevance
“…This was a little different with previous study that broken posterior wall related with higher rate of CL into the spinal canal. [5] It was because the maneuver to reduce fracture by inflating the balloon might further damage the fragile broken upper endplate, especially through transpedicle approach. Also CL through endplate cortical disruption may be very quick that it can be hard to stop.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was a little different with previous study that broken posterior wall related with higher rate of CL into the spinal canal. [5] It was because the maneuver to reduce fracture by inflating the balloon might further damage the fragile broken upper endplate, especially through transpedicle approach. Also CL through endplate cortical disruption may be very quick that it can be hard to stop.…”
Section: Discussionmentioning
confidence: 99%
“…[57] Cement leaking into the disc is found to increase the risk of new fractures of adjacent vertebral bodies. [8] In OCVFs with compromised vertebral body walls, the risk seemed to be higher as surgical maneuvers may further aggravate cortical fragments.…”
Section: Introductionmentioning
confidence: 99%
“…In this report we describe one patient with an incomplete osteoporotic burst fracture (AO type A3.1) and another patient with an AO type A1.3 fracture. Walter et al evaluated the frequency of complication with regard to the fracture type, and suggested that BKP can be considered as a safe procedure, even in the treatment of painful osteoporotic vertebral fractures of AO type A3.1 [14]. Our current case report demonstrates a cause of delayed neurological decline in those that undergoing BKP.…”
Section: Discussionmentioning
confidence: 60%
“…With the cementless application of the expandable titanium mesh cage, we did not see any of these complications leading to favorable results in complication rates when compared to standard methods [19, 20]. …”
Section: Discussionmentioning
confidence: 94%
“…This seems problematic, since, even after minor traumata, VCFs are amenable for involvement of the dorsal wall [14]. When taking this into consideration, cement-based treatment algorithms for VCF care are likely to induce cement-associated complications like leakage in the disc space or epidural space in more severe fracture types like burst fractures with dorsal wall involvement [15–20]. …”
Section: Introductionmentioning
confidence: 99%